Pendampingan Sistem Informasi Akuntansi Sederhana Melalui Klasifikasi Biaya Dan Alur Input Data Pada UMKM Industri Tahu Tempe - Marsyanda, Della; Emi Anggani , Putri; Novita, Dian; Muhammad Al Daffa Rizal (TRIDAYA: Jurnal Pengabdian kepada Masyarakat, 2026)
Poor financial record-keeping in production-based MSMEs directly hinders business owners from calculating production costs and making sound decisions. This community service activity aimed to assist the Suroso Group Tofu and Tempe Factory in implementing an accounting information system through cost classification and financial data input flows. Conducted on April 23, 2026, with 10 participants, the program comprised three sessions using a participatory action and direct demonstration approach: financial literacy introduction, production cost classification, and bookkeeping-based data input practice. The program's distinctiveness lies in its cost classification framework tailored specifically to the tofu and tempe production cycle, along with a Kahoot-based post-test evaluation. Results showed significant improvements: financial literacy rose from 40% to 82%, recording flow comprehension from 35% to 80%, data input ability from 28% to 75%, and participant engagement from 50% to 90% (average increase of 43.5%). These findings underscore the importance of context-specific, needs-based coaching for production MSMEs in building financial management capacity.